Sex differences in animal models of psychiatric disorders - Kokras, N; Dalla, C (Br J Pharmacol, 2014)
Psychiatric disorders are characterized by sex differences in their prevalence, symptomatology and treatment response. Animal models have been widely employed for the investigation of the neurobiology of such disorders and the discovery of new treatments. However, mostly male animals have been used in preclinical pharmacological studies. In this review, we highlight the need for the inclusion of both male and female animals in experimental studies aiming at gender-oriented prevention, diagnosis and treatment of psychiatric disorders. We present behavioural findings on sex differences from animal models of depression, anxiety, post-traumatic stress disorder, substance-related disorders, obsessive-compulsive disorder, schizophrenia, bipolar disorder and autism. Moreover, when available, we include studies conducted across different stages of the oestrous cycle. By inspection of the relevant literature, it is obvious that robust sex differences exist in models of all psychiatric disorders. However, many times results are conflicting, and no clear conclusion regarding the direction of sex differences and the effect of the oestrous cycle is drawn. Moreover, there is a lack of considerable amount of studies using psychiatric drugs in both male and female animals, in order to evaluate the differential response between the two sexes. Notably, while in most cases animal models successfully mimic drug response in both sexes, test parameters and treatment-sensitive behavioural indices are not always the same for male and female rodents. Thus, there is an increasing need to validate animal models for both sexes and use standard procedures across different laboratories.
Keywords: *Disease Models, Animal; *Mental Disorders; Animals; Humans; Sex Characteristics